Sub-anaesthetic bolus dose of intravenous ketamine for postoperative pain following caesarean section - Anil Kumar Bhiwal; Vartika Sharma; Karuna Sharma; Anuj Tripathi; Sunanda Gupta (Wolters Kluwer Medknow Publications, 2019)
Background: Effective postoperative analgesia following Caesarean Section is important because parturients are at a higher risk for thromboembolic events due to immobility, increased likelihood of developing postpartum depression (PPD) following inadequate pain control which also can interrupt breastfeeding. Ketamine at sub anesthetic doses has been considered to reduce postoperative pain and analgesic consumption following caesarean section. Aims: The aim of this study was to evaluate the efficacy of sub anesthetic doses of ketamine on post caesarean analgesia. Material and Methods: This randomized double blind, placebo controlled study was conducted on 108 parturients, divided into three groups (36 in each group);Group C- received 2 ml of 0.9% normal saline; Group Ka- received 0.15 mg/kg of ketamine (2 ml) and Group Kb- 0.3 mg/kg of ketamine (2 ml) after 5 min of delivery. Postoperatively VAS score, consumption of rescue analgesic in 24 h and adverse effects were recorded. Statistical analysis was done with Analysis of variance (ANOVA) for continuous variables and Chi-square test for categorical scale. P values less than 0.05 were considered significant. Results: Postoperative VAS scores were significantly higher in control group while the time to the first analgesic requirement was significantly prolonged in Ka group (5.44 ± 1.45 h) and Kb group (6.18 ± 1.61 h) as compared to the control group (4.97 ± 1.48 h). The total number of doses and total dose of rescue analgesic (tramadol) required in 24 hours was significantly less in the Ka group (194.44 ± 53.15 mg) and Kb group (152.78 ± 50.63 mg) as compared to group C (136.11 ± 48.71 mg. Conclusion: Administration of sub-anesthetic doses (0.15 mg/kg and 0.3 mg/kg) of intravenous ketamine enhanced postoperative analgesia and reduced the total rescue analgesic consumption in first 24 h following CS. Ketamine 0.3 mg/kg also increased the time to first postoperative rescue analgesic request.